Advances in the treatment options for vitiligo: activated low-dose cytokines-based therapy - Lotti, Torello; Hercogova, Jana; Fabrizi, Giuseppe (Expert opinion on pharmacotherapy, 2015)
INTRODUCTION: Vitiligo is a skin disorder characterized by a progressive depigmentation, which is caused by the loss of melanocytes at the cutaneous level. A shift of the immune system with a prevalence of T helper (Th)1/Th17 response instead of a Tregs/Th2 one and may be part of etiology of 10 vitiligo. AREAS COVERED: This review describes the major points of vitiligo onset and shows the cutting-edge results in the field of low-dose medicine in the treatment of dermatologic diseases and, in particular. in vitiligo. In this review on advances in vitiligo pharmacotherapy, the most pertinent recent publications are reported. Electronic databases such as PubMed were searched for terms 'low-dose medicine' or 'low dose and vitiligo' or 'low dose and psoriasis.' EXPERT OPINION: The availability of a systemic treatment for vitiligo, based on the oral administration of low-dose activated signaling molecules represents an opportunity for the dermatologists to overcome some specific pitfalls of currently available therapeutic protocols.
Keywords: melanocyty; vitiligo; Oxidative Stress; cytokiny; Signal Transduction; keratinocyty; melaniny; Melanins; lidé; Cytokines; oxidační stres; Keratinocytes; signální transdukce; Vitiligo; Melanocytes; Humans